Gel for battery pack and preparation method thereof
By developing a specific low-exothermic battery pack gel, using a specific proportion of components A and components B for catalytic reduction reactions, the problems of overheating and ignition during the filling process of lithium battery packs are solved, and the safety and mass production of battery packs are achieved.
Patent Information
- Application Number
- CN202310056053.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-01-16
AI Technical Summary
During the glue filling and packaging process of existing lithium battery packs, the polyurethane A&B double-phase gel emits a large amount of heat during the reaction, causing overheating of the battery pack and increasing the risk of fire.
A low-exothermic gel was developed, which was formed by mixing component A and component B in a specific mass ratio. Component A included epoxy resin and Al powder, and component B included polythiol, promoter, thioglycolic acid, gas silicon and Al(OH)3 or Al powder. The gel was formed by a catalytic reduction reaction, controlling the reaction temperature and reducing the exothermic amount.
It effectively reduces the risk of overheating of the battery pack during the glue filling process, reduces the possibility of fire, ensures the safety of the battery pack, and supports the mass production of the battery pack.
Smart Images

Figure BDA0004060567330000071 
Figure BDA0004060567330000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a gel for a battery pack and a preparation method thereof. Background Art
[0002] The battery pack is composed of n lithium battery cells connected in series and parallel. Lithium batteries are the main source of heat in the battery pack, but they are extremely sensitive to temperature. If the temperature exceeds or falls below a certain level, the lithium battery will malfunction or even catch fire, causing irreversible serious harm.
[0003] Lithium-ion batteries are sensitive to temperature. Too high a temperature will seriously affect the battery's charge and discharge performance and many characteristic parameters, such as internal resistance, voltage, SOC, available capacity, charge and discharge efficiency, and battery life. Overcharging, low-temperature charging, water immersion, internal short circuits in the battery, mechanical impact puncture, and other factors can cause thermal runaway. Moreover, ternary lithium batteries will decompose oxygen during thermal runaway, so fire trucks, fire extinguishers, and other fire-fighting devices are helpless. Therefore, such safety accidents are more serious than general fire consequences. The optimal operating temperature of common lithium batteries is within the range of 20℃~50℃±5℃.
[0004] Existing battery packs often use polyurethane adhesives to package battery packs. For example, CN108753235A discloses a reactive polyurethane hot melt adhesive for folding soft-package lithium-ion batteries, which aims to solve the problems in traditional side insulation packaging, such as the side tape is not firmly attached to the battery core body, the tape attachment position is inconsistent, and even the side lacks adhesive and metal leaks, the tape attachment effect is not good, and the consistency is poor; and the side is not firmly attached to the battery core body after side shaping. CN105122495 A discloses a polyurethane adhesive for forming a battery packaging material for obtaining a battery container. The polyurethane adhesive uses a main agent and a hardener. It can be a so-called two-liquid mixed adhesive in which the main agent and the hardener are mixed when used, or a one-liquid adhesive in which the main agent and the hardener are pre-mixed, or a type in which multiple main agents and / or multiple hardeners are mixed when used. However, the hardener will increase the activity of the entire reaction system, resulting in heat accumulation during the reaction and excessive temperature rise.
[0005] However, in the process of filling and packaging the battery pack of lithium batteries, especially lithium iron phosphate batteries, the existing polyurethane A&B two-phase gel will release a large amount of heat during the reaction, which will cause overheating in the battery pack, causing the battery diaphragm body to short-circuit and cause a fire.
[0006] Therefore, it is necessary to develop a low exothermic gel to prevent the problem of excessive gel exotherm causing the temperature to rise too quickly during the battery pack filling and packaging process. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a gel for a battery pack and a preparation method and application thereof. The gel is used in the filling process of the battery pack to reduce the risk of fire caused by overheating in the battery pack. Moreover, it is easy to fill the gel during the production process of the battery pack, and it is easy to realize mass production of the battery pack.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions.
[0009] A gel for a battery pack, comprising component A and component B; wherein:
[0010] Component A and component B are mixed in a mass ratio of (1-1.5):1 (e.g., 1.1:1, 1.2:1, 1.3:1, 1.4:1) to form the gel; wherein,
[0011] The component A includes epoxy resin C51, epoxy resin C52 and Al powder in a mass ratio of 1:(4.2-4.5):(4.5-4.8) (for example, 1:4.2:4.8, 1:4.3:4.7, 1:4.4:4.6, 1:4.5:4.5);
[0012] The B component includes a polymercaptan, a promoter, thioglycolic acid, gas silicon and Al(OH) in a mass ratio of 50:5:(3-6):(3-6):(30-39) (e.g., 50:5:3:3:39, 50:5:3:6:36, 50:5:6:3:36, 50:5:6:6:33, 50:5:4:4:37, 50:5:5:5:35). 3 ; Or, the B component includes polythiol, accelerator, thioglycolic acid, gas silicon and Al powder in a mass ratio of 50:5:(3-6):(3-6):(30-39) (for example, 50:5:3:3:39, 50:5:3:6:36, 50:5:6:3:36, 50:5:6:6:33, 50:5:4:4:37, 50:5:5:5:35).
[0013] In the above epoxy resins, C5 in C51 and C52 represents the fraction material in petroleum: C5 petroleum resin, also known as C5 resin, aliphatic hydrocarbon resin, is divided into three types: general type, blending type and primary color transparent type, with an average molecular weight of 1000-2500 g / mol. 1 in C51 / C52 represents bisphenol A epoxy resin, and 2 represents a mixture of No. 200 solvent gasoline, 2 toluene mixed solvent and bisphenol A epoxy resin. Epoxy resin C52 is more soluble in organic matter than epoxy resin C51, has better diffusivity, and can be filled more fully in the gel.
[0014] The gel for battery pack according to the present invention is formed by mixing component A and component B in a mass ratio of (1-1.5):1 (for example, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1), wherein component A is used for reaction, component B is used for catalysis, and after A and B are mixed, a catalytic reduction reaction occurs. When the ratio of A to B exceeds the above ratio range, the formed gel will produce adhesion, bubbles, and coexistence of solid and liquid.
[0015] According to the gel for battery pack of the present invention, the polythiol, accelerator, thioglycolic acid, gas silicon and Al(OH) in component B are 3 The mass ratio of (or Al powder) is 50:5:(3-6):(3-6):(30-39) (for example, by mass percentage, thioglycolic acid can be selected from 3%, 4%, 5%, 6%; gas silicon can be selected from 3%, 4%, 5%, 6%; Al(OH) 3 Or Al powder can be selected as 30%, 31%, 32%, 34%, 35%, 36%, 37%, 39%), which is conducive to better catalyzing the reaction of component A; exceeding this ratio range, the heat generated during the reaction of A and B is too large, and the heat generated accumulates, causing the temperature to rise rapidly; below this ratio range, mucus problems will occur and the reaction cannot be completed.
[0016] As a preferred embodiment, the gel for battery packs described above comprises the following components in mass percentage: 10% epoxy resin C51, 45% epoxy resin C52 and 45% Al. Preferably, the brand of epoxy resin C51 is E-45, and the brand of epoxy resin C52 is E-51.
[0017] The higher the grade of epoxy resin, the higher its oxygen content. The higher the oxygen content of epoxy resin, the higher its chemical activity and the more stable its performance after gelation. If low-grade epoxy resin is used, its oxygen content is low and its chemical activity is low, and the performance of the gel formed after the reaction will be poor. For example, E-51 epoxy resin means that the average epoxy value of epoxy resin is 51 / 100=0.51, and the epoxy value N / 100 is 0.48-0.54; E-44 epoxy resin means that the average epoxy value of epoxy resin is 44 / 100=0.44, and the epoxy value N / 100 is 0.41-0.47.
[0018] The E-51 resin used in the present invention has good performance. At the same time, due to the excellent high temperature heat resistance effect of E-51, the gel prepared by using it has a higher fire resistance temperature. Al powder is used for heat conduction, and it has the characteristic of fast heat dissipation. In component A, the reasonable amount of epoxy resin C51, epoxy resin C52 and Al powder is conducive to reducing the temperature when the gel for the battery pack begins to gel and reducing the temperature of the gel exothermic peak.
[0019] Preferably, the density of epoxy resin C51 and epoxy resin C52 is 1.9-2.3 g / cm 3 .
[0020] The gel for battery pack, as a preferred embodiment, the B component comprises the following components by mass percentage: 50% of polythiol, 5% of accelerator, 3-6% of thioglycolic acid (for example, 3%, 4%, 5%, 6%), 3% of gas silicon and Al(OH) 3 32-36% (for example, 33%, 34%, 35%, 35.5%); or, the B component includes the following ingredients in mass percentage: 50% polythiol, 5% accelerator, 3-6% thioglycolic acid (for example, 3%, 4%, 5%, 6%), 3% gas silicon and 32-36% Al powder (for example, 33%, 34%, 35%, 35.5%).
[0021] Preferably, the polythiol may be a polythiol used for low temperature epoxy resin curing, such as polythiol 504, whose molecular formula is C 7 H 16 S 6 ; The promoter includes magnesium manganate and the like.
[0022] In the present invention, component A is used as the base material of the gel for battery packs, and component B is used as a catalyst to catalyze the gelation reaction of the base material in the gel for battery packs. Among them, polythiol is a curing agent, and the role of thioglycolic acid is a curing agent in the catalytic reaction, which is used to delay the curing time of the epoxy resin adhesive. The more thioglycolic acid content, the slower the gelation reaction of the gel. The accelerator is used to promote the catalytic reaction at room temperature, and its purpose is to control the reaction temperature to prevent the temperature from rising too quickly. Al(OH) in component B 3 Or Al powder is an aluminum-based catalyst that can act as a heat conductor.
[0023] As a preferred embodiment, the gel for the battery pack can gel at a low temperature below 30°C (for example, 15°C, 18°C, 20°C, 25°C, 30°C). Preferably, the gel time of the gel at a temperature below 30°C is less than 72 hours.
[0024] The gel for the battery pack of the present invention is a low-temperature reactive two-phase resin gel.
[0025] Another aspect of the present invention further provides a method for preparing the above-mentioned gel for battery pack, comprising the following steps:
[0026] Component A and component B are weighed according to the formula, and the components A and B are evenly stirred in a vacuum to obtain the gel for the battery pack.
[0027] In the above preparation method, as a preferred embodiment, component A and component B are stirred in vacuum at room temperature for 20 minutes to make them evenly mixed, and the stirring speed is 500-600 rpm. Preferably, the room temperature is 20-30°C.
[0028] In the above preparation method, as a preferred embodiment, Al powder with a particle size of 600 mesh or more is used, that is, the particle size of the Al powder is 600 mesh or more to prevent adhesion during the gelation process.
[0029] In the above preparation method, as a preferred embodiment, during the vacuum stirring, the mass fraction accuracy is 5%.
[0030] In the present invention, the content of thioglycolic acid has different degrees of influence on the Shore hardness, exothermic peak and gel time. When the amount of thioglycolic acid added is large, the gel time of the obtained battery pack gel becomes longer, the exothermic peak decreases, and the Shore hardness decreases.
[0031] Another aspect of the present invention further provides the use of the gel for a battery pack. When the gel is used in a battery pack, it can be filled in the gaps between battery cells.
[0032] The gel of the present invention is applicable to all battery packs, and can prevent the battery pack from catching fire due to excessive temperature during the battery charge and discharge cycle.
[0033] In the present invention, under the condition that they do not conflict with each other, the above technical features can be freely combined to form a new technical solution.
[0034] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0035] (1) The gel prepared by the technical solution of the present invention can ensure that no overheating occurs when gelling occurs at a low temperature not exceeding 30°C;
[0036] (2) The use of the low-temperature gel of the present invention can solve the problem of high heat generation when using the A&B two-phase gel in the prior art; during the battery gel filling process, the risk of fire caused by heat in the battery is reduced, thereby ensuring the safety of the vehicle. DETAILED DESCRIPTION
[0037] The present invention will be described in detail below in conjunction with the embodiments. Each example is provided by way of explanation of the present invention and does not limit the present invention. In fact, it will be clear to those skilled in the art that modifications and variations may be made in the present invention without departing from the scope or spirit of the present invention. For example, a feature shown or described as a part of one embodiment may be used in another embodiment to produce yet another embodiment. Therefore, it is desired that the present invention includes such modifications and variations within the scope of the appended claims and their equivalents.
[0038] Example 1
[0039] A gel for a battery pack, comprising component A and component B, wherein component A and component B are mixed in a mass ratio of 1:1 to form the gel; wherein:
[0040] The component A comprises the following ingredients by weight:
[0041] 10 parts of epoxy resin C51 (E-45), 45 parts of epoxy resin C52 (E-51), and 45 parts of Al powder (aluminum powder); wherein the density of epoxy resin C51 (E-45) and epoxy resin C52 (E-51) is 1.9-2.3g / cm 3 ;
[0042] The B component comprises the following ingredients by weight:
[0043] 50 parts of polymercaptan, 5 parts of magnesium manganate (accelerator), 3 parts of thioglycolic acid, 3 parts of gas silicon, Al(OH) 3 39 parts. Among them, the polythiol is polythiol 504.
[0044] The preparation method of the gel comprises the following steps:
[0045] Weigh component A and component B according to the formula, and stir component A and component B under vacuum at room temperature for 20 minutes to mix them evenly, with a stirring speed of 500-600 rpm. Special attention should be paid to the following:
[0046] (1) During stirring, the mass fraction accuracy of various raw materials is: 5%;
[0047] (2) Use aluminum powder with a mesh size of 600 or above to prevent adhesion;
[0048] (3) The content of thioglycolic acid has different degrees of influence on the Shore hardness, exothermic peak and gel time.
[0049] The gel begins to gel at a temperature of 15-25°C.
[0050] Example 2
[0051] A gel for a battery pack, comprising component A and component B, wherein component A and component B are mixed in a mass ratio of 1:1 to form the gel; wherein:
[0052] The component A comprises the following ingredients by weight:
[0053] 10 parts of epoxy resin C51 (E-45), 45 parts of epoxy resin C52 (E-51) and 45 parts of Al powder (above 600 mesh); wherein the density of epoxy resin C51 (E-45) and epoxy resin C52 (E-51) is 1.9-2.3g / cm 3 ;
[0054] The B component comprises the following ingredients by weight:
[0055] 50 parts of polymercaptan, 5 parts of magnesium manganate, 6 parts of thioglycolic acid, 3 parts of gas silicon and Al(OH) 3 36 parts; wherein the polythiol adopts polythiol 504.
[0056] The preparation method of the gel is the same as that in Example 1.
[0057] The gel begins to gel at a temperature of 15-25°C and the gel time is less than 72 hours.
[0058] Example 3
[0059] This embodiment provides a gel for a battery pack, which differs from Embodiment 1 in that aluminum powder with a mesh size of 600 or more is used to replace Al(OH) in component B. 3 .
[0060] The gel begins to gel at a temperature of 15-25°C.
[0061] Example 4
[0062] A gel for a battery pack comprises a component A and a component B, wherein the component A and the component B are mixed at a mass ratio of 1.5:1 to form the gel; the specific components of the component A and the component B are the same as those in Example 1. The preparation method of the gel is the same as that in Example 1.
[0063] The gel begins to gel at a temperature of 15-25°C.
[0064] Comparative Example 1
[0065] This comparative example provides a gel, which does not add thioglycolic acid on the basis of Example 1, and the other components are the same as those in Example 1, and the preparation method is the same as the preparation method in Example 1.
[0066] Comparative Example 2
[0067] The difference between this comparative example and Example 1 is that epoxy resin C52 (E-44) is used instead of epoxy resin C52 (E-51) in Example 1. The density of epoxy resin C52 (E-44) is 1.9-2.3 g / cm 3 .
[0068] Comparative Example 3
[0069] A gel comprises component A and component B, wherein component A and component B are mixed in a mass ratio of 1:1 to form the gel; wherein:
[0070] The component A comprises the following ingredients by weight:
[0071] Epoxy resin C51 (E-44) 15 parts, epoxy resin C52 (E-51) 35 parts, Al powder (aluminum powder) 50 parts; wherein, the density of epoxy resin C51 (E-44) and epoxy resin C52 (E-51) is 1.9-2.3g / cm 3 ;
[0072] The B component comprises the following ingredients by weight:
[0073] 50 parts of polymercaptan, 5 parts of magnesium manganate, 3 parts of thioglycolic acid, 3 parts of gas silicon, Al(OH) 3 39 parts. Among them, the polythiol is polythiol 504.
[0074] Comparative Example 4
[0075] This example provides a gel for a battery pack, which differs from Example 1 in that component A includes the following components in parts by weight:
[0076] Epoxy resin C51 (E-45) 10 parts, epoxy resin C52 (E-51) 40 parts, Al powder (aluminum powder) 50 parts.
[0077] Performance Testing
[0078] Examples 1-4 and Comparative Examples 1-4 were subjected to gel, tensile shear strength and hardness tests.
[0079] Gel test: carried out according to GBT12007.7-1989.
[0080] Tensile shear strength test: carried out according to GBT-2794-2008.
[0081] Heat deformation temperature test: According to GBT1634.1-2004. Use YBJL-810 temperature recorder to collect exothermic temperature curve through multiple channels; derive exothermic peak temperature.
[0082] Table 1 shows the gel exothermic peak, gel time, tensile shear strength and hardness of the gels of Examples 1-4 and Comparative Examples 1-4.
[0083] Table 1 Gel exothermic peak, gel time, tensile shear strength and hardness of the gels prepared in Examples 1-4 and Comparative Examples 1-4
[0084]
[0085]
[0086] In the present invention, since a gel with a higher oxidation rate (oxidation activity) is used, the activity is higher. After increasing the reaction time, while releasing heat, the addition of aluminum powder enhances the thermal conductivity of the gel, which can prevent battery damage caused by heat accumulation. The sample prepared by this method has a heat release peak value of less than 60°C. During the process of filling the battery pack with glue, the current heat release temperature can be maintained within the range of 38±3°C. At the same time, a refrigeration device such as a fan or air conditioner needs to be provided therein to allow it to release heat better.
Claims
1. A gel for a battery pack, characterized in that: The gel comprises component A and component B; wherein, The component A and the component B are mixed in a mass ratio of (1-1.5):1 to form the gel; wherein, The component A comprises epoxy resin C51, epoxy resin C52 and Al powder in a mass ratio of 1:(4.2-4.5):(4.5-4.8); The B component includes a polythiol, a promoter, thioglycolic acid, gas silicon and Al(OH)3 in a mass ratio of 50:5:(3-6):(3-6):(30-39); or, the B component includes a polythiol, a promoter, thioglycolic acid, gas silicon and Al powder in a mass ratio of 50:5:(3-6):(3-6):(30-39); The brand of epoxy resin C51 is E-45, and the brand of epoxy resin C52 is E-51. The densities of epoxy resin C51 and epoxy resin C52 are 1.9-2.3 g / cm 3 .
2. The gel for battery pack according to claim 1, characterized in that: The component A comprises the following ingredients by mass percentage: 10% epoxy resin C51, 45% epoxy resin C52 and 45% Al; and / or, The B component comprises the following ingredients by mass percentage: 50% polythiol, 5% accelerator, 3-6% thioglycolic acid, 3% gas silicon and 32-36% Al(OH)3; or, the B component comprises the following ingredients by mass percentage: 50% polythiol, 5% accelerator, 3-6% thioglycolic acid, 3% gas silicon and 32-36% Al powder.
3. The gel for battery pack according to any one of claims 1 to 2, characterized in that: The polythiol is a polythiol used for curing low-temperature epoxy resin; and / or, The promoter includes magnesium manganate.
4. The gel for battery pack according to claim 3, characterized in that: The polythiol is polythiol 504, whose molecular formula is C7H 16 S6.
5. The gel for battery pack according to claim 1, characterized in that: The gel may be gelled at a low temperature below 30°C.
6. The gel for battery pack according to claim 5, characterized in that: The gel time of the gel at a temperature below 30° C. is less than 72 hours.
7. A method for preparing a gel for a battery pack according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Component A and component B are weighed according to the formula, and the components A and B are evenly stirred in a vacuum to obtain the gel for the battery pack.
8. The method for preparing the gel for battery pack according to claim 7, characterized in that: Component A and component B were stirred at room temperature under vacuum for 20 minutes to mix them evenly at a stirring speed of 500-600 rpm.
9. The method for preparing the gel for battery pack according to any one of claims 7 to 8, characterized in that: The particle size of the Al powder is 600 mesh or more.
10. An application of the gel for battery pack according to any one of claims 1 to 6, characterized in that: When the gel is applied to a battery pack, it fills the gaps between the battery cells.
Citation Information
Patent Citations
Polyurethane adhesive for packaging materials for batteries, packaging material for batteries, container for batteries, and battery
CN105122495A
Reactive type polyurethane hot melt adhesive for flexible packaging lithium ion battery edgefold
CN108753235A
Preparation method of polymercaptan curing adhesive
CN110776865A